If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 0.25(8x + 1) = 5x + 0.75(4x + -1) Reorder the terms: 2 + 0.25(1 + 8x) = 5x + 0.75(4x + -1) 2 + (1 * 0.25 + 8x * 0.25) = 5x + 0.75(4x + -1) 2 + (0.25 + 2x) = 5x + 0.75(4x + -1) Combine like terms: 2 + 0.25 = 2.25 2.25 + 2x = 5x + 0.75(4x + -1) Reorder the terms: 2.25 + 2x = 5x + 0.75(-1 + 4x) 2.25 + 2x = 5x + (-1 * 0.75 + 4x * 0.75) 2.25 + 2x = 5x + (-0.75 + 3x) Reorder the terms: 2.25 + 2x = -0.75 + 5x + 3x Combine like terms: 5x + 3x = 8x 2.25 + 2x = -0.75 + 8x Solving 2.25 + 2x = -0.75 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 2.25 + 2x + -8x = -0.75 + 8x + -8x Combine like terms: 2x + -8x = -6x 2.25 + -6x = -0.75 + 8x + -8x Combine like terms: 8x + -8x = 0 2.25 + -6x = -0.75 + 0 2.25 + -6x = -0.75 Add '-2.25' to each side of the equation. 2.25 + -2.25 + -6x = -0.75 + -2.25 Combine like terms: 2.25 + -2.25 = 0.00 0.00 + -6x = -0.75 + -2.25 -6x = -0.75 + -2.25 Combine like terms: -0.75 + -2.25 = -3 -6x = -3 Divide each side by '-6'. x = 0.5 Simplifying x = 0.5
| 2x-3=5x+4-3x | | 28=7x^2 | | 5k+3=3k-7 | | 60=15x^2 | | 3a^2-16a+21=0 | | 26x+18y=184 | | Cos^4x-4cos^2x=0 | | 3x-(5x/4)=12 | | X*0.75=9.3 | | 26x+13y=184 | | 5g-6-7-5g= | | 60+10x=180 | | 24m-m+6=42 | | 128=180 | | s^2-10+25=0 | | 2(4x+3)=7+5 | | 5h=1.5 | | 7/x-3/2=13/4 | | 2xy+y=6 | | 0.05x+.10(200-x)=.45x | | f=GH+Gh | | 3u+14=35 | | 2-4(2n+6)=3 | | 2y-9=11 | | 4+5(x)=39 | | 0.6(6+7x)-2x=0.4(4+3x)+3 | | 2(2n-5)=4 | | 13x+7y=42 | | 0=x^2+8x+11 | | 9y^2+18y+2=0 | | 3+5.2=1-2.8x | | 4x-4x-28=-28 |